Meta-Analisis Implementasi Penguatan Pendidikan Karakter di Sekolah Dasar - Khotimah, Husnul; Hermanto, Hermanto; Mujiono, Mujiono (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to evaluate both the successes and weaknesses of the implementation of Character Education Strengthening (Penguatan Pendidikan Karakter/PPK) in elementary schools in building students' character. The research method used is meta-analysis through a systematic literature review. This method was chosen because the primary studies reviewed in this research employed a qualitative approach. The study concludes that: (1) PPK is clearly defined in terms of its legal basis, concepts, objectives, and implementation strategies; (2) teachers and education personnel in elementary schools tend to have a limited understanding of the concept and implementation strategies of PPK; (3) elementary schools' readiness to implement PPK is generally still at the planning stage; and (4) the implementation of PPK has not yet produced the expected outcomes. Recommendations based on the findings of this meta-analysis   Keywords: Character Education Strengthening, Implementation, Teachers And Education Personnel